Obstructive sleep apnea and bone mineral density in obese patients - Mariani, Stefania (Dove Medical Press, 2012)
CONTEXT: Obesity and its co-morbidities may adversely affect bone mineral density (BMD). Obstructive sleep apnea (OSA) is a major complication of obesity. To date, the effects of OSA on BMD in obese patients have been poorly studied. OBJECTIVE: To examine whether the severity of OSA independently correlates with BMD in obese patients. METHODS: One hundred and fifteen obese subjects with OSA (Apnea/Hypopnea Index [AHI] ≥5 events per hour) were included in the study. BMD was measured at lumbar spine, total hip, and femoral neck by dual energy X-ray absorptiometry. Body mass index, lean mass, and representative measures of metabolic syndrome (waist circumference, fasting plasma glucose, blood pressure, HDL-cholesterol, triglycerides) and inflammation (ESR, CRP, fibrinogen) were also evaluated. RESULTS: BMD did not differ among obese individuals regardless of OSA severity. Correlation coefficient analysis for all the covariates showed a lack of association between AHI and BMD that was strongly influenced by age and weight. CONCLUSION: Our study does not support an independent association between AHI and BMD in obese patients. Controlled studies involving a greater number of patients are warranted.